Explaining young British Muslim men’s involvement in heroin and crack - Qasim, Mohammed (Criminology & criminal justice, 2018)
Recent years have seen an upsurge in the numbers of British Muslim men, particularly young British Muslim men aged from 18-35 involved in the sale of drugs. However, despite this alleged increase, very little is known as to what motivates young British Muslim men to become involved with drugs. This has led some commentators to deliberate whether there are perhaps cultural or religious reasons which may motivate Muslim men to become involved with drugs. This article, which is taken from a four-year phenomenological study (2010-2014) with a social group of young British Pakistani Muslim men who traded in heroin and crack argues that the young men (also known as The Boys) were not motivated by religious or cultural reasons but were instead motivated by a number of underlying issues. Factors such as deprivation, a need for status, the challenge of finding suitable paid employment, a reluctance to work in jobs that could affect status were all possible factors which explained why The Boys were involved in drugs.